Peningkatkan Pengetahuan dan Keterampilan Keluarga Ibu dalam Mendukung Kelancaran ASI dengan Pijat Oksitosin: Increasing Knowledge and Skills of the Mother's Family in Supporting the Smooth Breastfeeding with Oxytocin Massage - Dewi Andariya Ningsih; Innama Sakinah; Silaturrohmih Silaturrohmih; Tiara Indriani; Siti Hilmi Musyarrofah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Low milk production is one of the obstacles to exclusive breastfeeding. This community service activity will occur from December 2022 to February 2023. It starts from the time contract with the participants. It was collected in a place accessible to all participants. When the activity began, the pre-conference sheet was filled out first, followed by the presentation of the theory of oxytocin massage, questions and answers, and demonstrations. After that, it ends with filling out the post-conference sheet. Thirty-four breastfeeding mothers and 34 representatives of a family member (husband or mother's immediate family) participated in this activity. This community service activity has a significant effect on increasing breast milk production and prolactin levels. Therefore, oxytocin massage can be an alternative treatment for midwives, families, and other health workers to increase milk production during the puerperium.